WORK OF THE PRODUCER OF THE ANIMATED FILM ON THE PREPARATPRY PERIOD - M. Kosinova (Вестник университета)
The article discusses the activities of a producer of the animated film stage on the preparatory period. Considered such aspects as the idea, develop the concept, its visualization, search buyers, work on script, develop a production plan, budgeting, ensuring protection of materials against piracy. The article explores the relationship of the producer with other representatives of the audiovisual business, in particular with customer entertainment products, as the establishment of these linkages is very important on the preparatory period. Provides documentation compiled by the producer at the time.